Solve for z y=4^z

Math
y=4z
Rewrite the equation as 4z=y.
4z=y
Take the natural logarithm of both sides of the equation to remove the variable from the exponent.
ln(4z)=ln(y)
Expand ln(4z) by moving z outside the logarithm.
zln(4)=ln(y)
Divide each term by ln(4) and simplify.
Tap for more steps…
Divide each term in zln(4)=ln(y) by ln(4).
zln(4)ln(4)=ln(y)ln(4)
Cancel the common factor of ln(4).
Tap for more steps…
Cancel the common factor.
zln(4)ln(4)=ln(y)ln(4)
Divide z by 1.
z=ln(y)ln(4)
z=ln(y)ln(4)
z=ln(y)ln(4)
Solve for z y=4^z

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top